Pengaruh Disiplin Kerja, Kepemimpinan Kepala Sekolah, dan Lingkungan Kerja Terhadap Motivasi Berprestasi Guru Dengan Perilaku Inovatif Sebagai Variabel Moderasi - Utami, Sari; Kardoyo; Widiyanto (Universitas Negeri Semarang, 2025)
Teachers play a very important role in the success of education because they not only have the responsibility of delivering lesson material, but also must be able to be mentors, motivators, and role models for students. Teachers must have the achievement motivation to so they can be role models for students to progress and ultimately have a positive impact on the quality of education. However, teachers' motivation to achieve is still low, as can be seen from the low participation in various competitions, self-development, and writing books or scientific papers and learning innovations. This study examines the influence of work discipline, principal leadership, and work environment on the motivation to achieve of public junior high school teachers in group 01 in Semarang Regency, with innovative behavior as a moderating variable. Using a correlational quantitative design with SEM-PLS analysis on 154 teachers from a population of 250, the results show a significant positive influence of the three independent variables on achievement motivation. Meanwhile, the moderating effect of innovative behavior strengthens the influence of principal leadership and work environment on achievement motivation and weakens the influence of work discipline on achievement motivation.